Determinants of blood pressure in type 2 diabetic subjects with high occurrence of inadequate glycemic control - Codogno, Jamile Sanches [UNESP]; Fernandes, Rômulo Araújo [UNESP]; Freitas Jr., Ismael Forte [UNESP]; Monteiro, Henrique Luiz [UNESP] (My University, 2012)
Study design: Association study Objective: To analyze the association between different biological/behavioral risk factors and blood pressure in a sample of type 2 diabetes mellitus patients with poor glycemic control. Methods: A sample of 121 type 2 diabetic patients was selected in the Public Healthcare System in a middle size Brazilian city. Blood pressure was measured using an aneroid device, previously calibrated. Six determinants of blood pressure were taken into count: age, hypoglycemic agents, general obesity, abdominal obesity, eating behaviors and physical activity level. Results: The type 2 diabetic patients presented mean age of 60.1±8.9 years-old and, at least, one risk factor. Eating behaviors (OR adj= 0.31 [0.12-0.75]) and sports practice (OR adj= 0.12 [0.02-0.75]) constituted protective factors associated with lower systolic blood pressure. On the other hand, age was positively associated with high systolic blood pressure (OR adj= 3.81 [1.39-10.38]). Patients with 5-6 risk factors, presented higher values of systolic and (F= 3.857; p= 0.011 [post hoc with p= 0.039]), diastolic blood pressure (F= 4.158; p= 0.008 [post hoc with p= 0.036]) and increased occurrence of hypertension (p= 0.010). Conclusion: Our findings indicate that, behavioral variables were important determinants of blood pressure in type 2 diabetic patients with poor glycemic control and clustering of behavioral and biological risk factors increase the hypertension occurrence.
Keywords: Blood pressure; Diabetes mellitus; Diet; Physical activity; antidiabetic agent; abdominal obesity; adult; blood pressure; blood pressure measurement; Brazil; diastolic blood pressure; feeding behavior; female; glycemic control; human; hypertension; major clinical study; male; non insulin dependent diabetes mellitus; obesity; physical activity; risk factor; systolic blood pressure